2017
DOI: 10.15540/nr.4.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Event-related Potentials (ERP) in Cognitive Neuroscience Research and Applications

Abstract: This review is aimed at exploring the usefulness of measuring event-related potential (ERP) in cognitive tests and discusses several applications of the ERP technique. Analysis of ERP components is one of the most informative dynamic methods of investigation and monitoring of information processing stages in the human brain. Amplitude and latency of ERP components at specified topographies reflect early sensory perception processes and higher level processing including attention, cortical inhibition, memory up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 124 publications
0
23
0
Order By: Relevance
“…The differences occurred in the ANT, which required sustained attention and applied to the P200 potential. The literature links the potential to early evaluation and classification of stimuli [33,34]. Previous studies, whose procedures included the ANT, identified some differences in the CNV, P100, N100 and P300 potentials [32,67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences occurred in the ANT, which required sustained attention and applied to the P200 potential. The literature links the potential to early evaluation and classification of stimuli [33,34]. Previous studies, whose procedures included the ANT, identified some differences in the CNV, P100, N100 and P300 potentials [32,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…The contingent negative variation (CNV) is also related to attention stimulation processes, which are observed when a stimulus is preceded by a cue [32]. The P200 potential is, in turn, associated with the early classification of stimuli [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Hallahan (1999) reported seven framing models in public relations, depending on what is framed: situations, attributes, choices, actions, issues, responsibility and news. In contrast, Pan and Kosicki (1993) argued that news frames are based on four structural dimensions: syntactical, script, thematic, and rhetorical. Gamson and Lasch (1983) argued that organizations are capable of creating argumentative packages about events.…”
Section: Defines Framing Asmentioning
confidence: 99%
“…As for Pz channel, a positive peak is found around 200 ms, which represent the P200 of ERP component. The P100 and P200 is waveform components that are commonly related to the early processing of attention state [39]. According to the waveforms shown in the graph, the P100 mostly distributed over the frontal cortex, whereas the P200 is often distributed in the parietal cortex.…”
Section: B Grand-averaged Event-related Potentialmentioning
confidence: 99%